Nitrogen-doped carbon metal oxide composite material and preparation method thereof, negative electrode material, negative electrode plate and lithium ion battery

By doping nitrogen and carbon elements on the surface of Co2NiO4, a nitrogen-doped carbon metal oxide composite material is formed, which solves the problems of poor conductivity and volume expansion of the negative electrode material of lithium-ion batteries, improves the charge and discharge performance and cycle stability, and meets the High energy density and long lifespan requirements.

CN119170761APending Publication Date: 2024-12-20CHINA FAW CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411092019.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing lithium-ion battery anode materials such as Co2NiO4 are poor in conductivity and volume expansion effects, which are difficult to meet the needs of high energy density and long cycle life.

Method used

Using nitrogen-doped carbon metal oxide composite material, the nitrogen and carbon elements are dispersed on the surface of Co2NiO4 to improve conductivity and reduce volume expansion. The Ni-Co PBA precursor is used as a template for high-temperature pyrolysis preparation, forming a high specific surface area and porosity Co2NiO4-N-C material.

Benefits of technology

It significantly improves the charge and discharge specific capacity, rate performance and cycle stability of the material, enhances the transport efficiency and structural stability of lithium ions, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170761A_ABST
    Figure CN119170761A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery negative electrode materials, in particular to a nitrogen-doped carbon metal oxide composite material and a preparation method thereof, a negative electrode material, a negative electrode plate and a lithium ion battery. The nitrogen-doped carbon metal oxide composite material comprises Co2NiO4 with a hollow cubic structure, and a nitrogen element and a carbon element which are dispersed on the surface of the Co2NiO4. The material is good in conductivity, low in resistance and good in structural stability, volume expansion caused by Li < + > embedding in the circulation process can be relieved, the volume expansion effect in the material charging and discharging process can be inhibited, the electrode polarization effect can be reduced, and the charging and discharging specific capacity, the rate capability and the circulation stability of the material can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a nitrogen-doped carbon metal oxide composite material and a preparation method thereof, a negative electrode material, a negative electrode sheet and a lithium ion battery. Background Art

[0002] At present, the specific capacity of commercial graphite anodes is close to its theoretical limit, which is difficult to meet the increasing demand for battery life. Although the specific capacity of traditional metal oxides and Si anodes is high, the serious volume effect during the charge and discharge process can easily cause structural collapse and material pulverization, which affects the cycle performance. With the continuous improvement of performance requirements such as energy density and cycle life, it is particularly important to develop and synthesize lithium-ion batteries (LIBs) with excellent performance. So far, there have been many alternative materials, such as transition metal oxides, metal alloys and other carbonaceous materials. They have high theoretical capacity, especially transition metal oxides, which have attracted much attention due to their large theoretical capacity (over 700mAh / g), which is 2 to 3 times higher than that of commercial graphite anodes (372mAh / g). However, some shortcomings of transition metal oxides hinder their practical application as battery anode materials, such as poor stability and rate performance due to excessive volume expansion and inherent high resistance during charge and discharge.

[0003] Compared with binary metal oxides, ternary metal oxides exhibit lower resistance due to the lower threshold energy for electron transfer between positive ions. For example, Co3O4 and Ni x Co 3-x The conductivity of O4 is 3.1×10 -5 S cm -1 and 0.1~0.3S·cm -1 Therefore, a large number of ternary metal oxide systems such as CuCo2O4, MgCo2O4, Co2NiO4 and their hybrid materials have been widely explored. Among these ternary metal oxides, Co2NiO4 can react with Li + Chemical reaction, the theoretical specific capacity is about 891mAh g -1 , and has been widely studied as an excellent negative electrode material for lithium-ion batteries. However, due to its poor conductivity and volume expansion effect, the charge and discharge capacity of the electrode material decays rapidly and the rate performance is poor. These problems seriously affect the application of Co2NiO4 electrode materials as negative electrode materials for power lithium-ion batteries.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first object of the present invention is to provide a nitrogen-doped carbon metal oxide composite material, which has good conductivity and low resistance, and is helpful to alleviate the Li + The volume expansion caused by embedding and its good structural stability can inhibit the volume expansion effect during the material's charge and discharge process, reduce the electrode polarization effect, and effectively improve the material's charge and discharge specific capacity, rate performance and cycle stability. This solves the problem of poor stability and rate performance of existing transition metal oxides due to their poor conductivity, excessive volume expansion during charge and discharge, and inherent high resistance.

[0006] The second purpose of the present invention is to provide a method for preparing a nitrogen-doped carbon-metal oxide composite material. The nitrogen-doped carbon-metal oxide composite material prepared by this method can reduce the volume expansion of Co2NiO4, increase the contact area between Co2NiO4 and the electrolyte, shorten the ion transmission distance, improve the conductivity of Co2NiO4, and improve the rate performance and cycle performance of the nitrogen-doped carbon-metal oxide composite material.

[0007] The third object of the present invention is to provide a negative electrode material, which has excellent electrochemical properties and broad application prospects.

[0008] A fourth object of the present invention is to provide a negative electrode sheet having high capacity, and excellent rate performance and cycle performance.

[0009] A fifth object of the present invention is to provide a lithium ion battery having high capacity, good rate performance and excellent cycle performance.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] The present invention firstly provides a nitrogen-doped carbon metal oxide composite material, comprising Co2NiO4 with a hollow cubic structure, and nitrogen elements and carbon elements dispersed on the surface of the Co2NiO4.

[0012] Furthermore, the specific surface area of ​​the nitrogen-doped carbon-metal oxide composite material is 220 to 260 m 2 ·g -1 .

[0013] Furthermore, the pore volume of the nitrogen-doped carbon-metal oxide composite material is 0.29 to 0.34 cm 3 ·g -1 .

[0014] Furthermore, the mass fraction of nitrogen in the nitrogen-doped carbon-metal oxide composite material is 8.0% to 9.0%.

[0015] Furthermore, the mass fraction of carbon element in the nitrogen-doped carbon-metal oxide composite material is 9.0% to 10.0%.

[0016] Furthermore, a lithium-ion battery containing the nitrogen-doped carbon-metal oxide composite material has a high conductivity at 0.15 A·g -1 Discharge capacity after 100 cycles ≥850mAh·g -1 .

[0017] The present invention further provides a method for preparing the nitrogen-doped carbon-metal oxide composite material, comprising the following steps:

[0018] A mixed solution containing a complexing agent and nickel nitrate is mixed with a potassium cobalt cyanide solution and reacted, and then the solid-liquid is separated and dried to obtain a Ni-Co PBA precursor;

[0019] The Ni-Co PBA precursor is calcined to obtain the nitrogen-doped carbon metal oxide composite material.

[0020] Furthermore, the mixing is performed according to a mass ratio of the complexing agent, nickel nitrate and potassium cobalt cyanide of 1.5-2.5:0.8-1.5:0.6-1.2.

[0021] Furthermore, the complexing agent includes sodium citrate and / or citric acid.

[0022] Furthermore, the mixing is performed according to a mass ratio of the complexing agent, nickel nitrate and potassium cobalt cyanide of 1.7-2.5:1.0-1.5:0.8-1.2.

[0023] Furthermore, the temperature of the mixing and reaction is 10-35°C.

[0024] Furthermore, the mixing and reaction time is 12 to 24 hours.

[0025] Furthermore, a washing step is included between the solid-liquid separation and the drying.

[0026] Furthermore, the drying temperature is 45 to 100° C., and the drying time is 12 to 48 hours.

[0027] Furthermore, the calcination temperature is 300-600°C.

[0028] Furthermore, the calcination time is 1 to 4 hours.

[0029] Furthermore, the heating rate of the calcination is 1 to 5°C min -1 .

[0030] Furthermore, the calcination atmosphere includes air atmosphere and / or oxygen atmosphere.

[0031] The present invention further provides a negative electrode material, comprising the nitrogen-doped carbon-metal oxide composite material.

[0032] The present invention further provides a negative electrode sheet, comprising the negative electrode material.

[0033] The present invention also provides a lithium ion battery, comprising the negative electrode sheet.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) The nitrogen-doped carbon metal oxide composite material provided by the present invention greatly promotes charge dynamics, can effectively improve the electron transfer between composite material particles, prevent the occurrence of side reactions between the composite material and the electrolyte, inhibit the volume expansion effect during the charge and discharge process of the composite material, thereby reducing the electrode polarization effect, and effectively improve the charge and discharge specific capacity, rate performance and cycle stability of the composite material. Co2NiO4 has a hollow cubic structure, which can provide more active sites for full penetration of electrolytes, increase the probability of effective collision between ions and materials, and effectively shorten the transmission distance of electrons and ions.

[0036] (2) The nitrogen-doped carbon-metal oxide composite material provided by the present invention not only has the advantages of high capacity of metal compounds, but also has high specific surface area and high porosity, which effectively promotes the transport of lithium ions and can withstand Li + The high stress induced by continuous intercalation / deintercalation can further enhance the electrolyte diffusion rate, resulting in efficient ion transport and structural stability.

[0037] (3) The nitrogen-doped carbon-metal oxide composite material provided by the present invention has high capacity, good rate performance and excellent cycle performance.

[0038] (4) The preparation method of the nitrogen-doped carbon metal oxide composite material provided by the present invention uses the Ni-Co PBA precursor as a sacrificial template to prepare the Co2NiO4-NC composite negative electrode material, which can not only effectively promote the + transport, and can withstand Li +The high stress caused by continuous embedding / de-embedding can further improve the electrolyte diffusion rate, and has efficient ion transmission and structural stability. At the same time, the present invention uses Ni-Co PBA as a precursor sacrificial template and uses the metal oxide derivative Co2NiO4-NC prepared by high-temperature pyrolysis as the electrode material. In addition to having the advantages of controllable chemical composition and being able to retain the high porosity and large specific surface area of ​​Ni-Co PBA, it also retains its original cubic structure. The cubic structure can provide more active sites for the full penetration of electrolytes, increase the probability of effective collision between ions and materials, and effectively shorten the transmission distance of electrons and ions.

[0039] (5) The preparation method of the nitrogen-doped carbon metal oxide composite material provided by the present invention decomposes the cyanide group after calcination to obtain nitrogen-doped carbon, which effectively improves the electron transmission between the composite material particles and improves the electrochemical performance of the composite material.

[0040] (6) The preparation method of the nitrogen-doped carbon metal oxide composite material provided by the present invention, the metal oxide derived from Ni-Co PBA not only has the advantage of high capacity of metal compounds, but also retains the characteristics of high specific surface area and high porosity of the precursor. When used as a negative electrode material for LIBs, the large specific surface area and high porosity can improve the permeability of the electrolyte and further improve the utilization rate of active sites. The pore structure also provides a larger area for the contact between the electrode and the electrolyte. These factors are conducive to the adsorption and transfer of lithium ions. At the same time, the presence of nitrogen-doped carbon improves the conductivity of the metal oxide, which helps to alleviate the Li + The volume expansion caused by embedding increases the overall structural stability of the composite material, thereby bringing about better cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 A schematic flow chart of a method for preparing a nitrogen-doped carbon-metal oxide composite material provided by the present invention;

[0043] Figure 2 This is a SEM image of the Ni-Co PBA precursor prepared in Example 1 provided by the present invention;

[0044] Figure 3 This is a SEM image of the nitrogen-doped carbon-metal oxide composite material prepared in Example 1 provided by the present invention;

[0045] Figure 4 The XRD pattern of the Ni-Co PBA precursor prepared in Example 1 provided by the present invention;

[0046] Figure 5 A comparison diagram of Raman spectra of the Ni-Co PBA precursor and the nitrogen-doped carbon metal oxide composite material Co2NiO4-NC prepared in Example 1 provided by the present invention;

[0047] Figure 6 This is a mapping element analysis diagram of the nitrogen-doped carbon metal oxide composite material Co2NiO4-NC prepared in Example 1 provided by the present invention. DETAILED DESCRIPTION

[0048] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0049] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0050] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0051] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.

[0052] In a first aspect, the present invention provides a nitrogen-doped carbon metal oxide composite material Co2NiO4-NC, which includes Co2NiO4 having a hollow (i.e., hollow) cubic structure, and nitrogen and carbon elements uniformly dispersed on the surface of the Co2NiO4. The nitrogen and carbon elements are in a uniformly doped state, and the carbon element mainly exists in the form of amorphous carbon.

[0053] The nitrogen-doped carbon-metal oxide composite material provided by the present invention greatly promotes charge dynamics, can effectively improve electron transfer between composite material particles, prevent the occurrence of side reactions between the composite material and the electrolyte, inhibit the volume expansion effect of the composite material during charge and discharge, thereby reducing the electrode polarization effect, and effectively improve the charge and discharge specific capacity, rate performance and cycle stability of the composite material.

[0054] Co2NiO4 has a hollow cubic structure, which can provide more active sites for full penetration of electrolytes, increase the probability of effective collision between ions and materials, and effectively shorten the transmission distance of electrons and ions.

[0055] The nitrogen-doped carbon-metal oxide composite material provided by the present invention not only has the advantages of high capacity of metal compounds, but also has high specific surface area and high porosity, which effectively promotes the transport of lithium ions and can withstand Li + The high stress induced by continuous intercalation / deintercalation can further enhance the electrolyte diffusion rate, resulting in efficient ion transport and structural stability.

[0056] In some specific embodiments, the nitrogen-doped carbon-metal oxide composite material has a high specific surface area, wherein the specific surface area of ​​the nitrogen-doped carbon-metal oxide composite material is 220 to 260 m 2 ·g -1 , including but not limited to 220m 2 ·g -1 、230m 2 ·g -1 、240m 2 ·g -1 、250m 2 ·g -1 、260m 2 ·g -1 Any point value in or any range of values ​​between them.

[0057] In some specific embodiments, the nitrogen-doped carbon-metal oxide composite material has a high porosity, wherein the pore volume of the nitrogen-doped carbon-metal oxide composite material is 0.29 to 0.34 cm 3 ·g -1 , including but not limited to 0.29cm 3 ·g-1 、0.30cm 3 ·g -1 、0.31cm 3 ·g -1 、0.32cm 3 ·g -1 、0.33cm 3 ·g -1 、0.34cm 3 ·g -1 Any point value in or any range of values ​​between them.

[0058] In some specific embodiments, in order to further improve the electrochemical properties of the nitrogen-doped carbon-metal oxide composite material, the mass fraction of the nitrogen element in the nitrogen-doped carbon-metal oxide composite material is 8.0% to 9.0%, including but not limited to 8.0%, 8.1%, 8.2%, 8.3%, 8.4%, 8.5%, 8.6%, 8.7%, 8.8%, 8.9%, 9.0%, any one of the point values ​​or the range value between any two of them.

[0059] In some specific embodiments, in order to further improve the electrochemical properties of the nitrogen-doped carbon-metal oxide composite material, the mass fraction of the carbon element in the nitrogen-doped carbon-metal oxide composite material is 9.0% to 10.0%, including but not limited to any point value of 9.0%, 9.1%, 9.2%, 9.3%, 9.4%, 9.5%, 9.6%, 9.7%, 9.8%, 9.9%, 10.0% or the range value between any two of them.

[0060] In some specific embodiments, a lithium-ion battery containing the nitrogen-doped carbon-metal oxide composite material has a -1 Discharge capacity after 100 cycles ≥850mAh·g -1 , including but not limited to 860mAh·g -1 , 900mAh g -1 , 950mAh·g -1 , 1000mAh g -1 、1100mAh·g -1 , 1200mAh g -1 , 1300mAh g -1 , 1400mAh g -1 , 1500mAh g -1 , 1550mAh·g -1 , 1600mAh g -1Any point value or range value between any two of them. It can be seen that the lithium ion battery made of the nitrogen-doped carbon metal oxide composite material provided by the present invention has excellent cycle performance. In some specific embodiments, the lithium ion battery containing the nitrogen-doped carbon metal oxide composite material has an excellent cycle performance at 0.15A·g -1 Discharge capacity ≥1800mAh·g -1 ; Including but not limited to 1800mAh·g -1 、1810mAh·g -1 , 1820mAh·g -1 、1830mAh·g -1 、1840mAh·g -1 、1850mAh·g -1 Any point value in or any range of values ​​between them.

[0061] In some specific embodiments, a lithium-ion battery containing the nitrogen-doped carbon-metal oxide composite material has a -1 Discharge capacity ≥1400mAh·g -1 ; Including but not limited to 1400mAh·g -1 , 1420mAh·g -1 、1430mAh·g -1 , 1450mAh·g -1 , 1460mAh·g -1 、1470mAh·g -1 , 1480mAh·g -1 , 1500mAh g -1 Any point value in or any range of values ​​between them.

[0062] In some specific embodiments, a lithium-ion battery containing the nitrogen-doped carbon-metal oxide composite material has a -1 Discharge capacity ≥1100mAh·g -1 ; Including but not limited to 1100mAh·g -1 、1110mAh·g -1 、1120mAh·g -1 、1130mAh·g -1 、1140mAh·g -1 、1150mAh·g -1 、1160mAh·g -1 Any point value in or any range of values ​​between them.

[0063] In some specific embodiments, a lithium-ion battery containing the nitrogen-doped carbon-metal oxide composite material has a-1 Discharge capacity ≥1000mAh·g -1 ; Including but not limited to 1000mAh·g -1 、1010mAh·g -1 , 1020mAh·g -1 、1030mAh·g -1 , 1040mAh·g -1 , 1050mAh·g -1 Any point value in or any range of values ​​between them.

[0064] In some specific embodiments, a lithium-ion battery containing the nitrogen-doped carbon-metal oxide composite material has a -1 Discharge capacity ≥800mAh·g -1 ; Including but not limited to 800mAh·g -1 、810mAh·g -1 、820mAh·g -1 、830mAh·g -1 、840mAh·g -1 、850mAh·g -1 、870mAh·g -1 , 900mAh g -1 Any point value in or any range of values ​​between them.

[0065] It can be seen that the lithium ion battery made of the nitrogen-doped carbon metal oxide composite material provided by the present invention has high capacity and excellent rate performance.

[0066] In a second aspect, the present invention provides a method for preparing the nitrogen-doped carbon-metal oxide composite material, or a method for preparing a nitrogen-doped carbon-metal oxide (Co2NiO4-NC) composite negative electrode material derived from a Prussian blue analogue, which specifically comprises the following steps:

[0067] Potassium cobalt cyanide (K3[Co(CN)6]) is dissolved in water and stirred evenly to obtain an aqueous solution of potassium cobalt cyanide, wherein the stirring time can be 10 to 60 minutes.

[0068] Nickel nitrate or nickel nitrate hexahydrate and a complexing agent are dissolved in water, and stirred evenly to obtain a mixed aqueous solution containing the complexing agent and nickel nitrate. The stirring time can be 10 to 60 minutes.

[0069] A mixed aqueous solution containing a complexing agent and nickel nitrate is quickly mixed and stirred with an aqueous solution of potassium cobalt cyanide to carry out a coprecipitation reaction, followed by solid-liquid separation and drying to obtain a Ni-Co PBA precursor. Among them, the solid-liquid separation can adopt any separation method commonly used in the art, such as centrifugal separation. As an example, the rotation speed of the centrifugal separation is 3500 to 10000 r / min. The chemical formula of the Ni-Co PBA precursor is Ni3[Co(CN)6]2·12H2O and / or Ni3[Co(CN)6]2. Prussian blue analog (PBA) is a new type of metal organic framework material. The Ni-Co PBA precursor has a cubic structure, in which the cyano group plays the role of connecting transition metal ions. It has a special structure of two metal centers connected by cyanide chains in the octahedral position.

[0070] The Ni-Co PBA precursor is calcined, the Ni-Co PBA precursor is pyrolyzed at high temperature, and the nitrogen-doped carbon metal oxide composite material is obtained after cooling.

[0071] The preparation method of the nitrogen-doped carbon metal oxide composite material provided by the present invention uses Ni-Co PBA precursor as a sacrificial template to prepare Co2NiO4-NC composite negative electrode material, which can not only effectively promote Li + transport, and can withstand Li + The high stress induced by continuous intercalation / deintercalation can further enhance the electrolyte diffusion rate, resulting in efficient ion transport and structural stability.

[0072] At the same time, the present invention uses Ni-Co PBA as a precursor sacrificial template and adopts the metal oxide derivative Co2NiO4-NC prepared by high-temperature pyrolysis as the electrode material. In addition to having the advantages of controllable chemical composition and retaining the high porosity and large specific surface area of ​​Ni-Co PBA, it also retains its original cubic structure. The cubic structure can provide more active sites for sufficient penetration of electrolytes, increase the probability of effective collision between ions and materials, and effectively shorten the transmission distance of electrons and ions.

[0073] After calcination, the cyanide groups decompose to obtain nitrogen-doped carbon, which effectively improves the electron transport between the composite particles and enhances the electrochemical performance of the composite.

[0074] The Co2NiO4-NC obtained after calcination promotes the redox reaction kinetics with the help of more active sites, and the heteroatom N can improve the electrode-electrolyte wettability and provide additional lithium storage sites.

[0075] Ni-Co PBA-derived metal oxides not only have the advantages of high capacity of metal compounds, but also retain the characteristics of high specific surface area and high porosity of the precursor. When used as negative electrode materials for LIBs, the large specific surface area and high porosity can improve the permeability of the electrolyte and further improve the utilization of active sites. The pore structure also provides a larger area for the contact between the electrode and the electrolyte. These factors are conducive to the adsorption and transfer of lithium ions. At the same time, the presence of nitrogen-doped carbon improves the conductivity of the metal oxide, which helps to alleviate the Li-ion cycle. + The volume expansion caused by embedding increases the overall structural stability of the composite material, thereby bringing about better cycle stability.

[0076] The nitrogen-doped carbon metal oxide composite material prepared by coprecipitation and calcination in the present invention can reduce excessive volume expansion during charging and discharging, and improve lithium storage capacity and rate performance.

[0077] In addition, the preparation method provided by the present invention has a simple operation process, high safety, and can achieve mass production.

[0078] In some specific embodiments, in order to improve the electrochemical properties of nitrogen-doped carbon metal oxide composites, the raw materials are mixed according to the mass ratio of the complexing agent, nickel nitrate and potassium cobalt cyanide of 1.5-2.5 (including but not limited to 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, or any range between two values): 0.8-1.5 (including but not limited to 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, or any range between two values): 0.6-1.2 (including but not limited to 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, or any range between two values).

[0079] In some specific embodiments, the complexing agent includes sodium citrate and / or citric acid.

[0080] Taking sodium citrate as a complexing agent, the schematic diagram of the preparation method of nitrogen-doped carbon metal oxide composite material is shown in Figure 1 shown.

[0081] In some specific implementations, in order to further improve the electrochemical performance of the nitrogen-doped carbon metal oxide composite material, the mixing is performed according to a mass ratio of the complexing agent, nickel nitrate, and potassium cobalt cyanide of 1.7-2.5:1.0-1.5:0.8-1.2.

[0082] In some specific implementations, the amount of water added can be set as needed. For example, in the mixed material obtained after the mixing, the mass ratio of potassium cobalt cyanide to water is 0.5-1.2:100-400.

[0083] In some specific embodiments, the mixing and the reaction are carried out at room temperature, for example, the temperature of the mixing and reaction is 10-35°C; including but not limited to any point value of 10°C, 15°C, 20°C, 25°C, 30°C, 35°C or a range value between any two of them.

[0084] In some specific embodiments, the mixing and reaction time is 12 to 24 hours, including but not limited to any point value of 12 hours, 14 hours, 15 hours, 16 hours, 18 hours, 20 hours, 22 hours, and 24 hours, or a range value between any two of them.

[0085] In some specific embodiments, a washing step is further included between the solid-liquid separation and the drying.

[0086] In some specific embodiments, water and ethanol are used for the washing respectively.

[0087] In some specific embodiments, the drying temperature is 45-100°C, including but not limited to any point value of 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C or a range value between any two of them; preferably 60-100°C.

[0088] In some specific embodiments, the drying time is 12 to 48 hours, including but not limited to any point value of 12h, 14h, 15h, 16h, 18h, 20h, 22h, 24h, 28h, 30h, 32h, 36h, 40h, 44h, 48h or a range value between any two of them; preferably 12 to 24h.

[0089] In some specific embodiments, the calcination temperature is 300-600°C, including but not limited to any point value of 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or a range value between any two of them; preferably 400-600°C.

[0090] In some specific embodiments, the calcination time is 1 to 4 hours, including but not limited to any one of 1 hour, 2 hours, 3 hours, and 4 hours or a range between any two of them; preferably 2 to 4 hours.

[0091] In some specific embodiments, the heating rate of the calcination is 1 to 5 °C·min -1; Including but not limited to 1℃·min -1 、2℃·min -1 、3℃·min -1 、4℃·min -1 、5℃·min -1 Any point value or any range value between two; preferably 2 to 4 ° C. min -1 .

[0092] In some specific embodiments, the calcination may be performed using any calcination equipment commonly used in the art, such as a tube furnace, but is not limited thereto.

[0093] In some specific embodiments, the calcination atmosphere includes air atmosphere and / or oxygen atmosphere.

[0094] In a third aspect, the present invention provides a negative electrode material, comprising the nitrogen-doped carbon-metal oxide composite material.

[0095] The nitrogen-doped carbon-metal oxide composite material provided by the present invention has excellent electrochemical performance as a negative electrode material and has broad application prospects.

[0096] In a fourth aspect, the present invention provides a negative electrode sheet comprising the negative electrode material.

[0097] The negative electrode sheet has high capacity, as well as excellent rate performance and cycle performance.

[0098] Optionally, the negative electrode sheet further includes a binder and a conductive agent.

[0099] In a fifth aspect, the present invention provides a lithium-ion battery, including the negative electrode sheet, which is not limited by the present invention.

[0100] The lithium-ion battery has high capacity, good rate performance and excellent cycle performance.

[0101] Optionally, the lithium-ion battery further includes a positive electrode sheet, a separator and an electrolyte, which is not limited in the present invention.

[0102] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0103] Example 1

[0104] The preparation method of the nitrogen-doped carbon metal oxide composite material provided in this embodiment includes the following steps: at room temperature, first dissolve 0.82g of potassium cobalt cyanide in 100mL of water, stir for 10min, and mark the solution as A. Then dissolve 1.76g of sodium citrate and 1.16g of nickel nitrate hexahydrate in 150mL of water, stir for 10min, and mark the solution as B. That is, the mass ratio of the complexing agent, nickel nitrate and potassium cobalt cyanide is 1.76:1.16:0.82. Pour the prepared solution A into solution B quickly, stir continuously and react for 12h at room temperature (25°C). Then collect the reactants obtained after the reaction by centrifugation at a speed of 8000r / min, wash with water and ethanol several times, and put them into a 60°C oven for drying for 12h after washing to obtain Ni-Co PBA powder. The Ni-CoPBA powder prepared above was calcined in a tubular furnace at 400° C. in an air atmosphere for 2 h at a heating rate of 2° C. / min to obtain a nitrogen-doped carbon metal oxide composite material Co2NiO4-NC.

[0105] The SEM image of the Ni-CoPBA precursor prepared in this example is shown in Figure 2 shown.

[0106] The SEM image of the nitrogen-doped carbon-metal oxide composite material prepared in this example is shown in Figure 3 As shown. Figure 3 It can be seen that Co2NiO4 has a hollow cubic structure.

[0107] The XRD pattern of the Ni-CoPBA precursor prepared in this example is shown in Figure 4 shown.

[0108] The Raman spectra comparison of the Ni-CoPBA precursor and the nitrogen-doped carbon metal oxide composite material Co2NiO4-NC prepared in this example are shown in Figure 5 As shown. Figure 5 It can be seen that compared with Ni-CoPBA, the cyanide absorption band (C≡N) is at 2184.3 cm -1 This confirms that the cyano group decomposes to form nitrogen-doped carbon.

[0109] The elemental analysis of the nitrogen-doped carbon metal oxide composite material Co2NiO4-NC prepared in this example is shown in the following figure: Figure 6 shown.

[0110] Example 2

[0111] The preparation method of the nitrogen-doped carbon metal oxide composite material provided in this embodiment includes the following steps: at room temperature, first dissolve 1.0g of potassium cobalt cyanide in 100mL of water, stir for 10min, and mark the solution as A. Then dissolve 1.9g of sodium citrate and 1.2g of nickel nitrate hexahydrate in 150mL of water, stir for 10min, and mark the solution as B. That is, the mass ratio of the complexing agent, nickel nitrate and potassium cobalt cyanide is 1.9:1.2:1.0. The prepared solution A is quickly poured into solution B, and the mixture is continuously stirred and reacted for 12h at room temperature (25°C). Then the reactant obtained after the reaction is collected by centrifugation at a speed of 8000r / min, and washed with water and ethanol several times. After washing, it is placed in a 60°C oven and dried for 12h to obtain Ni-Co PBA powder. The Ni-Co PBA powder prepared above is calcined in an air atmosphere at 400°C for 2h in a tubular furnace at a heating rate of 2°C / min to obtain a nitrogen-doped carbon metal oxide composite material Co2NiO4-NC.

[0112] Example 3

[0113] The preparation method of the nitrogen-doped carbon metal oxide composite material provided in this embodiment includes the following steps: at room temperature, first dissolve 1.0g of potassium cobalt cyanide in 100mL of water, stir for 10min, and mark the solution as A. Then dissolve 2.0g of sodium citrate and 1.2g of nickel nitrate hexahydrate in 150mL of water, stir for 10min, and mark the solution as B. That is, the mass ratio of the complexing agent, nickel nitrate and potassium cobalt cyanide is 2.0:1.2:1.0. The prepared solution A is quickly poured into solution B, and the mixture is continuously stirred and reacted for 12h at room temperature (25°C). Then the reactant obtained after the reaction is collected by centrifugation at a speed of 10000r / min, and washed with water and ethanol several times. After washing, it is placed in a 60°C oven and dried for 24h to obtain Ni-Co PBA powder. The Ni-Co PBA powder prepared above is calcined in an air atmosphere at 400°C for 2h in a tubular furnace at a heating rate of 3°C / min to obtain a nitrogen-doped carbon metal oxide composite material Co2NiO4-NC.

[0114] Example 4

[0115] The preparation method of the nitrogen-doped carbon metal oxide composite material provided in this embodiment includes the following steps: at room temperature, first dissolve 1.1g of potassium cobalt cyanide in 100mL of water, stir for 10min, and mark the solution as A. Then dissolve 2.2g of sodium citrate and 1.2g of nickel nitrate hexahydrate in 150mL of water, stir for 10min, and mark the solution as B. That is, the mass ratio of the complexing agent, nickel nitrate and potassium cobalt cyanide is 2.2:1.2:1.1. The prepared solution A is quickly poured into solution B, and the mixture is continuously stirred and reacted for 24h at room temperature (25°C). Then the reactant obtained after the reaction is collected by centrifugation at a speed of 10000r / min, and washed with water and ethanol several times. After washing, it is placed in a 60°C oven and dried for 24h to obtain Ni-Co PBA powder. The Ni-Co PBA powder prepared above is calcined in an air atmosphere at 500°C for 2h in a tubular furnace at a heating rate of 3°C / min to obtain a nitrogen-doped carbon metal oxide composite material Co2NiO4-NC.

[0116] Example 5

[0117] The preparation method of the nitrogen-doped carbon metal oxide composite material provided in this embodiment includes the following steps: at room temperature, first dissolve 1.1g of potassium cobalt cyanide in 100mL of water, stir for 10min, and mark the solution as A. Then dissolve 2.3g of sodium citrate and 1.3g of nickel nitrate hexahydrate in 150mL of water, stir for 10min, and mark the solution as B. That is, the mass ratio of the complexing agent, nickel nitrate and potassium cobalt cyanide is 2.3:1.3:1.1. The prepared solution A is quickly poured into solution B, and the mixture is continuously stirred and reacted for 12h at room temperature (25°C). Then the reactant obtained after the reaction is collected by centrifugation at a speed of 10000r / min, and washed with water and ethanol several times. After washing, it is placed in a 60°C oven and dried for 24h to obtain Ni-Co PBA powder. The Ni-Co PBA powder prepared above is calcined in an air atmosphere at 500°C for 3h at a heating rate of 4°C / min in a tubular furnace to obtain a nitrogen-doped carbon metal oxide composite material Co2NiO4-NC.

[0118] Example 6

[0119] The preparation method of the nitrogen-doped carbon metal oxide composite material provided in this embodiment includes the following steps: at room temperature, first dissolve 1.2g of potassium cobalt cyanide in 100mL of water, stir for 10min, and mark the solution as A. Then dissolve 2.4g of sodium citrate and 1.5g of nickel nitrate hexahydrate in 150mL of water, stir for 10min, and mark the solution as B. That is, the mass ratio of the complexing agent, nickel nitrate and potassium cobalt cyanide is 2.4:1.5:1.2. The prepared solution A is quickly poured into solution B, and the mixture is continuously stirred and reacted for 12h at room temperature (25°C). Then the reactant obtained after the reaction is collected by centrifugation at a speed of 10000r / min, and washed with water and ethanol several times. After washing, it is placed in a 60°C oven and dried for 24h to obtain Ni-Co PBA powder. The Ni-Co PBA powder prepared above is calcined in an air atmosphere at 600°C for 3h at a heating rate of 4°C / min in a tubular furnace to obtain a nitrogen-doped carbon metal oxide composite material Co2NiO4-NC.

[0120] Example 7

[0121] The preparation method of the nitrogen-doped carbon metal oxide composite material provided in this embodiment includes the following steps: at room temperature, first dissolve 1.2g of potassium cobalt cyanide in 100mL of water, stir for 10min, and mark the solution as A. Then dissolve 2.5g of sodium citrate and 1.5g of nickel nitrate hexahydrate in 150mL of water, stir for 10min, and mark the solution as B. That is, the mass ratio of the complexing agent, nickel nitrate and potassium cobalt cyanide is 2.5:1.5:1.2. The prepared solution A is quickly poured into solution B, and the mixture is continuously stirred and reacted for 24h at room temperature (25°C). Then the reactant obtained after the reaction is collected by centrifugation at a speed of 10000r / min, and washed with water and ethanol several times. After washing, it is placed in a 60°C oven and dried for 24h to obtain Ni-Co PBA powder. The Ni-Co PBA powder prepared above is calcined in an air atmosphere at 600°C for 4h in a tubular furnace at a heating rate of 3°C / min to obtain a nitrogen-doped carbon metal oxide composite material Co2NiO4-NC.

[0122] Example 8

[0123] The preparation method of the nitrogen-doped carbon metal oxide composite material provided in this embodiment includes the following steps: at room temperature, first dissolve 1.2g of potassium cobalt cyanide in 150mL of water, stir for 30min, and mark the solution as A. Then dissolve 2.5g of citric acid and 1.5g of nickel nitrate hexahydrate in 200mL of water, stir for 30min, and mark the solution as B. That is, the mass ratio of the complexing agent, nickel nitrate and potassium cobalt cyanide is 2.5:1.5:1.2. The prepared solution A is quickly poured into solution B, and the mixture is continuously stirred and reacted for 24h at room temperature (20°C). Then the reactant obtained after the reaction is collected by centrifugation at a speed of 10000r / min, and washed with water and ethanol several times. After washing, it is placed in an 80°C oven and dried for 24h to obtain Ni-Co PBA powder. The Ni-Co PBA powder prepared above is calcined in an air atmosphere at 400°C for 4h in a tubular furnace at a heating rate of 2°C / min to obtain a nitrogen-doped carbon metal oxide composite material Co2NiO4-NC.

[0124] Comparative Example 1

[0125] The negative electrode material provided in this comparative example is the Ni-Co PBA powder prepared in Example 8.

[0126] Comparative Example 2

[0127] The preparation method of the negative electrode material provided in this comparative example comprises the following steps:

[0128] 1 mmol Co(NO3)2·6H2O was dissolved in 10 mL of deionized water containing 6 mg of CTAB (hexadecyltrimethylammonium bromide, as a complexing agent) to obtain a mixed solution. The mixed solution was quickly injected into 70 mL of deionized water containing 4.5 g of 2-methylimidazole, stirred evenly, centrifuged at 6000 rpm for 3 min, then washed with deionized water and ethanol several times, and dried in an oven at 60°C for 12 h to obtain a ZIF-67 cubic sample (cobalt dimethylimidazole).

[0129] 20 mg of the ZIF-67 cubic sample prepared above was ultrasonically dispersed in 25 ml of anhydrous ethanol, and then 0.3 mmol of nickel chloride was added thereto and stirred at room temperature for 1 h. The resulting solution was then transferred to a 50 mL reactor and reacted at 130 ° C for 3 h. After naturally cooling to room temperature, it was washed with deionized water several times and dried at 60 ° C to collect the powder. The above powder was then heated to 300 ° C in a N2 atmosphere at 300 ° C at a heating rate of 1 ° C / min and annealed for 2 h, then uniformly dispersed in 25 mL of deionized water, stirred at room temperature for 1 h, washed with deionized water, and dried at 60 ° C to obtain the negative electrode material Co2NiO4.

[0130] Comparative Example 3

[0131] The preparation method of the negative electrode material provided in this comparative example comprises the following steps: 0.2375g NiCl2·6H2O and 0.2379g CoCl2·6H2O are dissolved in 50mL deionized water and stirred for 5min, and then 0.0888g NH4F and 0.18g urea are added thereto. The above solution is then transferred into an 80mL autoclave and heated at 120°C for 12h. After the reaction is completed, the solid material is collected by centrifugation, washed with deionized water and ethanol several times, and then dried at 60°C for 12h. Finally, the dried powder is heated to 350°C in a N2 atmosphere at 350°C at a heating rate of 2°C / min for annealing for 2h, and then cooled to room temperature to obtain the negative electrode material Co2NiO4.

[0132] Comparative Example 4

[0133] The preparation method of the negative electrode material provided in this comparative example comprises the following steps: Ni(NO3)2·6H2O, Co(NO3)2·6H2O and Na2CO3 are placed in a mixed solvent of ethylene glycol and water (the mass ratio of ethylene glycol and water is 1:1) in a molar ratio of 1:2:3 and stirred evenly, and then 7mL of a 28% ammonia solution is added thereto, and after stirring evenly, the resulting mixed solution is transferred to a blast oven and heated at 150°C for 3h. After cooling, the precipitate is rinsed with distilled water and ethanol, and dried in an oven at 60°C for 12h to obtain a precursor. Finally, the above precursor is annealed in a muffle furnace at 350°C for 2h to obtain the negative electrode material NiCo2O4.

[0134] Comparative Example 5

[0135] The preparation method of the negative electrode material provided in this comparative example is basically the same as that of Example 8, except that the mass of potassium cobalt cyanide is replaced with 2.5 g, that is, the mass ratio of the complexing agent, nickel nitrate and potassium cobalt cyanide is 2.5:1.5:2.5.

[0136] Comparative Example 6

[0137] The preparation method of the negative electrode material provided in this comparative example is basically the same as that of Example 8, except that the mass of potassium cobalt cyanide is replaced with 0.3 g, that is, the mass ratio of the complexing agent, nickel nitrate and potassium cobalt cyanide is 2.5:1.5:0.3.

[0138] The specific surface area, porosity, and mass fraction of nitrogen and carbon in each material of the nitrogen-doped carbon-metal oxide composite material prepared in each embodiment and the negative electrode material prepared in each comparative example were tested respectively. The results are shown in Table 1.

[0139] Table 1 Physical and chemical performance indicators

[0140]

[0141]

[0142] Experimental example

[0143] The nitrogen-doped carbon-metal oxide composite materials prepared in each embodiment and the negative electrode materials prepared in each comparative example were respectively used as active materials to prepare lithium-ion batteries according to the following method: the active material, acetylene black and polyvinylidene fluoride (PVDF) were mixed in N-methyl-2-pyrrolidone (NMP) in a weight ratio of 7:2:1, and then evenly distributed in 8 cm 2 The negative electrode sheet was obtained by drying in a vacuum oven at 60°C for 20 h, with an active material loading of 2 mg / cm 2 The button cell is CR2032 and is assembled in a glove box. The protective gas in the glove box is argon, and the water and oxygen partial pressures are both less than 1ppm. A half-cell is assembled using lithium foil as the counter electrode.

[0144] Among them, the discharge specific capacity of the half-cell assembled by the nitrogen-doped carbon metal oxide composite material of Example 1 at different rates and 0.15A·g -1 The discharge capacity results after 100 cycles at the same rate are shown in Table 2. The discharge capacity results after 100 cycles of the half-cells assembled in each embodiment and each comparative example are shown in Table 3.

[0145] Table 2 Electrochemical performance test results of half-cell of Example 1

[0146]

[0147]

[0148] Table 3 Electrochemical performance test results of half-cells assembled in each embodiment and each comparative example

[0149] Group Number of cycles <![CDATA[Discharge specific capacity (mAh·g -1 )]]> <![CDATA[Current density (A·g -1 )]]> Example 1 100 1550 0.15 Example 2 100 1032 0.15 Example 3 100 1011 0.15 Example 4 100 1064 0.15 Example 5 100 991 0.15 Example 6 100 939 0.15 Example 7 100 913 0.15 Example 8 100 863 0.15 Comparative Example 1 100 256 0.15 Comparative Example 2 100 529 0.15 Comparative Example 3 100 834 0.15 Comparative Example 4 100 435 0.15 Comparative Example 5 100 810 0.15 Comparative Example 6 100 760 0.15

[0150] It can be seen from Table 2 and Table 3 that the nitrogen-doped carbon metal oxide composite materials provided by each embodiment have high capacity, excellent rate performance and excellent cycle performance after being assembled into a lithium-ion battery. However, after the negative electrode materials prepared in each comparative example are assembled into a lithium-ion battery, the cycle performance is significantly reduced.

[0151] In summary, the nitrogen-doped carbon metal oxide composite material provided by the present invention has good electrical conductivity and low resistance, and can effectively improve the charge and discharge specific capacity, rate performance and cycle stability of the battery prepared therefrom.

[0152] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A nitrogen-doped carbon-metal oxide composite material, characterized in that: The invention comprises Co2NiO4 having a hollow cubic structure, and nitrogen elements and carbon elements dispersed on the surface of the Co2NiO4.

2. The nitrogen-doped carbon-metal oxide composite material according to claim 1, characterized in that: At least one of the following conditions is met: (1) The specific surface area of ​​the nitrogen-doped carbon-metal oxide composite material is 220 to 260 m 2 ·g -1 ; (2) The pore volume of the nitrogen-doped carbon-metal oxide composite material is 0.29 to 0.34 cm 3 ·g -1 .

3. The nitrogen-doped carbon-metal oxide composite material according to claim 1, characterized in that: The mass fraction of nitrogen in the nitrogen-doped carbon-metal oxide composite material is 8.0% to 9.0%; And / or, the mass fraction of carbon element in the nitrogen-doped carbon-metal oxide composite material is 9.0% to 10.0%.

4. The nitrogen-doped carbon-metal oxide composite material according to claim 1, characterized in that: The lithium ion battery containing the nitrogen-doped carbon metal oxide composite material has a high conductivity at 0.15A·g -1 Discharge capacity after 100 cycles ≥850mAh·g -1 .

5. The method for preparing the nitrogen-doped carbon-metal oxide composite material according to any one of claims 1 to 4, characterized in that: The steps include: A mixed solution containing a complexing agent and nickel nitrate is mixed with a potassium cobalt cyanide solution and reacted, and then the solid-liquid is separated and dried to obtain a Ni-Co PBA precursor; The Ni-Co PBA precursor is calcined to obtain the nitrogen-doped carbon metal oxide composite material.

6. The method for preparing the nitrogen-doped carbon-metal oxide composite material according to claim 5, characterized in that: The mixing is performed according to a mass ratio of the complexing agent, nickel nitrate, and potassium cobalt cyanide of 1.5-2.5:0.8-1.5:0.6-1.2; And / or, the complexing agent includes sodium citrate and / or citric acid.

7. The method for preparing the nitrogen-doped carbon-metal oxide composite material according to claim 5, characterized in that: The mixing is performed according to a mass ratio of the complexing agent, nickel nitrate and potassium cobalt cyanide of 1.7-2.5:1.0-1.5:0.8-1.

2.

8. The method for preparing the nitrogen-doped carbon-metal oxide composite material according to claim 5, characterized in that: At least one of the following conditions is met: (1) The temperature of the mixing and reaction is 10 to 35° C.; (2) The mixing and reaction time is 12 to 24 hours; (3) between the solid-liquid separation and the drying, a washing step is also included; (4) The drying temperature is 45 to 100° C. and the drying time is 12 to 48 hours.

9. The method for preparing the nitrogen-doped carbon-metal oxide composite material according to claim 5, characterized in that: At least one of the following conditions is met: (1) The calcination temperature is 300 to 600° C.; (2) the calcination time is 1 to 4 hours; (3) The heating rate of the calcination is 1 to 5 °C min -1 ; (4) The calcination atmosphere includes air atmosphere and / or oxygen atmosphere.

10. A negative electrode material, characterized in that: The invention comprises the nitrogen-doped carbon-metal oxide composite material as claimed in any one of claims 1 to 4.

11. A negative electrode sheet, characterized in that: Comprising the negative electrode material as claimed in claim 10.

12. A lithium ion battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 11.

Citation Information

Cited By

  • Ni and Co bimetallic derivative catalytic material, preparation method and application

    CN120790156A

  • Preparation method and application of fluorine-doped Co2NiO4 (at) RGO three-dimensional heterostructure electrode material and sodium ion battery

    CN121641971A

  • A method for preparing a fluorine-doped Co2NiO4@RGO three-dimensional heterostructure electrode material, its application, and a sodium-ion battery.

    CN121641971B